Induction of bystander effect in root meristem of soybean seedlings after γ-irradiation - German, O.; Legostaeva, O.; Babyka, O. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2019)
The bystander effect refers to the non-target effects of ionizing radiation and it is the occurrence of radiation damages in the cells that have not been exposed to direct action of ionizing radiation. The aim of the study is to investigate the possibility of forming the “bystander effect” during the germination of irradiated and intact seeds of some soybean Glycine max (L.) Mer. varieties in the common aquatic environment. The soybean seeds of the Raiduga and Sprytna varieties (obtained by selection) and the genetically modified Apollo variety had been exposed to γ-radiation at a dose of 40 Gy. The mitotic activity of the seedlings root meristem cells of irradiated (IR) and intact (IN) seeds, as well as intact seeds, which were germinated in the same aqueous medium together with irradiated (INIR), was analyzed. The similar levels of mitotic activity were observed in seedlings of breeding varieties in “IN” variant, while cells in genetically modified variety divided more intensively. Radiation exposure in a dose of 40 Gy increased the level of mitotic activity in all varieties. The values of the mitotic indices increased 2 times in the varieties of Raiduga and Sprytna. The increase in Apollo variety was less significant, but this may be due to a high level of mitotic activity in the control variant. Irradiation also contributed to the appearance of chromosomal aberrations: fragments and bridges. The increase in mitotic activity in the meristem of the studied varieties to the mentioned levels may indicate the presence of a pool of meristem cells that can accelerate the passage of phases of the mitotic cycle under extreme conditions. Mitotic activity increased in the “INIR” variant in all investigated varieties. The largest excess over the “IN” was in Sprytna, a little less in the variety Raiduga. The proliferative activity in the Apollo variety meristem remained almost unchanged. Thus, the work shows the possibility of a “bystander effect” forming under the condition of joint germination of irradiated and intact seeds in the common aquatic environment. The intensity of “bystander effect” formation depends on the genotype and start mitotic potential.